1983
DOI: 10.1172/jci110844
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Propranolol and Lidocaine through the Rat Blood-Brain Barrier. PRIMARY ROLE OF GLOBULIN-BOUND DRUG

Abstract: A B S T R A C T Basic lipophilic drugs such as propranolol and lidocaine are strongly bound by a1-acid glycoprotein, also called orosomucoid. Although the liver is known to rapidly clear plasma protein-bound propranolol or lidocaine, it is generally regarded that peripheral tissues, such as brain or heart, are only exposed to the small fraction of drug that is free or dialyzable in vitro. The "free drug" hypothesis is subjected to direct empiric testing in the present studies using human sera and an in vivo ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(66 citation statements)
references
References 35 publications
3
62
0
1
Order By: Relevance
“…For instance, Weisiger et al 13,16) presented the albumin receptor-mediated transport concept to account for the transport of fatty acid, sulfobromophthalein and bilirubin into the liver, and Forker and Luxon14, 15) suggested the presence of albumin-mediated transport in the liver for rose bengal and taurocholate. Subsequently, we also found an albumin-mediated hepatic uptake of warfarin using the multiple indicator dilution method.31) Pardridge et al 18,19) suggested a "free intermediate model" to explain the transport of many substances such as steroid hormone and l-propranolol (PL) into the brain. Recent in vivo studied showed that the transit time of albumin through the liver and brain is not delayed compared with that of an extracellular marker such as sucrose.32,33) In addition, in vitro studies using liver plasma membranes34) and brain microvessels33) could not detect any specific binding to albumin and failed to support the albumin receptor-mediated transport concept in either liver or brain.…”
Section: Resultsmentioning
confidence: 78%
“…For instance, Weisiger et al 13,16) presented the albumin receptor-mediated transport concept to account for the transport of fatty acid, sulfobromophthalein and bilirubin into the liver, and Forker and Luxon14, 15) suggested the presence of albumin-mediated transport in the liver for rose bengal and taurocholate. Subsequently, we also found an albumin-mediated hepatic uptake of warfarin using the multiple indicator dilution method.31) Pardridge et al 18,19) suggested a "free intermediate model" to explain the transport of many substances such as steroid hormone and l-propranolol (PL) into the brain. Recent in vivo studied showed that the transit time of albumin through the liver and brain is not delayed compared with that of an extracellular marker such as sucrose.32,33) In addition, in vitro studies using liver plasma membranes34) and brain microvessels33) could not detect any specific binding to albumin and failed to support the albumin receptor-mediated transport concept in either liver or brain.…”
Section: Resultsmentioning
confidence: 78%
“…These results, together with the observation that transport was dependent on pH but independent of sodium and membrane potential ( Figures 5A and 5B), suggest that I and II share a common H +/ OC transporter with pyrilamine. 31 To further explore the fate of prodrugs after they are taken up into BCECs, we examined their transendothelial transport in a BCEC-AC coculture model of the BBB. This model relies on transwell culture inserts to create 'contact through feet' interface for interactions between the two cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Pardridge et al 2 showed that influx of lidocaine to the brain is not restricted by the blood brain barrier. Pajeva et al 24 also reported that lidocaine does not interact with phospholipids constructing tumour cells expressing P-gp.…”
Section: Measurement Of Lidocaine Megx and Bupivacaine In Plasma Andmentioning
confidence: 99%
“…Previous studies have shown that influx of globulinbound as well as free lidocaine into the brain is not prevented by the blood brain barrier. 2 However, the blood brain barrier permeability of bupivacaine, a widely used long-acting local anesthetic with high lipid solubility and more than 90% protein binding, has not been examined.…”
mentioning
confidence: 99%